Resource depletion and capital accumulation under catastrophic risk: The role of stochastic thresholds and stock pollution - Eric Nævdal; Jon Vislie (University of Oslo, Department of Economics, 2012)
An intertemporal optimal strategy for accumulation of reversible capital and management of an exhaustible resource is analyzed for a global economy when resource depletion generates discharges that add to a stock pollutant that affects the likelihood for hitting a tipping point or threshold of unknown location, causing a random disembodied technical regress. We characterize the optimal strategy by imposing the notion precautionary tax on current extraction. Such a tax will internalize future expected damages or expected welfare loss should a threshold be hit. With reversible capital the presence of a stochastic threshold should speed up accumulation as long as no threshold is hit so as to build up a buffer or stock for future consumption should a threshold be hit.
Keywords: C61; Q51; Q54; 330; Catastrophic risk and stochastic thresholds; capital accumulation; precautionary taxation; stock pollution; resource extraction; Ökosteuer; Investition; Umweltbelastung; Theorie